Determination of dissociation constants via quantitative mass spectrometry - Schulte, Jonathan; Tants, Jan-Niklas; von Ehr, Julian; Schlundt, Andreas; Morgner, Nina (Frontiers in Analytical Science, 2023)
The interplay of biomolecules governs all cellular processes. Qualitative analysis of such interactions between biomolecules as well as the quantitative assessment of their binding affinities are essential for the understanding of biochemical mechanisms. As scientific interest therefore moves beyond pure structural investigation, methods that allow for the investigation of such interactions become increasingly relevant. In this perspective we outline classical methods that are applicable for the determination of binding constants and highlight specifically mass spectrometry based methods. The use of mass spectrometry to gain quantitative information about binding affinities however is a still developing field. Here, we discuss different approaches, which emerged over the last years to determine dissociation constants (KD) with MS based methods. Specifically, we highlight the recent development of quantitative Laser Induced Liquid Bead Ion Desorption (qLILBID) mass spectrometry for the example of double stranded DNAs as well as for different RNA – RNA binding protein systems. We show that qLILBID can successfully be used for the top down investigation of complexes and their KD values ranging from low nM to low µM affinities.